3D measurement of gears based on a line structured light sensor - Guo, Xiaozhong; Shi, Zhaoyao; Yu, Bo; Zhao, Baoya; Li, Ke; Sun, Yanqiang (Precision engineering, 2020)
Gears are core components of transmission systems. The current trend of gear measurements is the rapid and full digitization. To rapidly obtain information on the three-dimensional (3D) shape of the gear tooth flank, a 3D point cloud measurement system based on a line structure light sensor and high precision air floating rotary table is proposed. The system can acquire more than 1.5 million 3D data points on one side of the gear tooth flank within less than 5 s. In this study, the measured 3D point cloud data is used to calculate the profile error, pitch error, then compared to those obtained from traditional contact measurements. In addition, tooth flank error was evaluated. The results show that the 3D point cloud measurement system can perform fast and accurately in 3D measurements of gears and it is a novel system for gear measurement and error calculation. •New Gear points measurement system has been established.•Traditional accuracy parameters have been evaluated.•New gear tooth 3d error has been discussed and calculated.•A new method of gear measurement and evaluation was developed.